2018
DOI: 10.3892/ol.2018.9431
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‑miR‑376c‑3p targets Cyclin D1 and induces G1‑cell cycle arrest in neuroblastoma cells

Abstract: High-risk neuroblastoma is the most aggressive form of cancer in children. The estimated survival of children with high-risk neuroblastoma is 40-50% compared with low and intermediate risk neuroblastoma, which is >98 and 90-95%, respectively. In addition, patients with high-risk neuroblastoma often experience relapse following intensive treatments with standard chemotherapeutic drugs. Therefore alternative strategies are required to address this problem. MicroRNAs (miRNAs/miRs) are small, endogenously expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…1B). The correlation analysis indicated that low miR-376c-3p expression was significantly correlated with lymph node metastasis (P=0.002; Table SI), which was consistent with previous studies that demonstrated that miR-376c-3 served as a cancer suppressor (22)(23)(24)(25). Among the potential targets of miR-376c-3ppredicted using online software TargetScan (http://www.targetscan.org/vert_72/), RAB2A has been reported to be involved in breast cancer development (28,29).…”
Section: Aberrant Expression Of Mir-376c-3p and Rab2a In Breast Cancersupporting
confidence: 90%
See 2 more Smart Citations
“…1B). The correlation analysis indicated that low miR-376c-3p expression was significantly correlated with lymph node metastasis (P=0.002; Table SI), which was consistent with previous studies that demonstrated that miR-376c-3 served as a cancer suppressor (22)(23)(24)(25). Among the potential targets of miR-376c-3ppredicted using online software TargetScan (http://www.targetscan.org/vert_72/), RAB2A has been reported to be involved in breast cancer development (28,29).…”
Section: Aberrant Expression Of Mir-376c-3p and Rab2a In Breast Cancersupporting
confidence: 90%
“…1A). Among the miRNAs, miR-376c-3p has been reported to participate in the development of several types of cancer (22)(23)(24)(25)(26)(27), and is downregulated in breast cancer (33)(34)(35)(36). However, how miRNAs affect breast cancer progression is not completely understood.…”
Section: Aberrant Expression Of Mir-376c-3p and Rab2a In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically, we speculated that circPIP5K1A might post-transcriptionally modulate gene expression by functioning as a ceRNA in GC based on the data that circPIP5K1A was mainly distributed in cytoplasm, and thereby it was primarily needed to find out the specific miRNA. Subsequently, through bioinformatics prediction and molecular experiments, miR-376c-3p was screened out due to its notable high binding ability with circPIP5K1A and its close association with the progression of human malignancies [25][26][27]. Then miR-376c-3p was confirmed to be dramatically downregulated in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificdata www.nature.com/scientificdata/ (expressed in arbitrary fluorescence units). Quantitative N 0 values have been used in previous publications [19][20][21][22][23][24] . Determining N 0 has several advantages over relative quantification.…”
Section: Gene Symbol Refseq Accessionmentioning
confidence: 99%